Optimizing Instagram as a Digital Marketing Medium: a Descriptive Study of Tukangbangunandimedan by PT. Satu Shaff Bersama - Dina Indah Permatasari (Sean Institute, 2025)
Social media is very useful for business because it can help entrepreneurs to find target markets, find out what customers want, expand market reach, expand brands, and so on. find out information about competitors. This study focuses on the effectiveness of Instagram social media as a digital marketing medium as seen from how far the reach of the Instagram account @tukangbangunandimedan reaches other Instagram users so that it can attract consumers. The purpose of this study is to determine whether Instagram is effective as a digital marketing medium for the company PT. Satu Shaff Bersama. The method used in this study is a qualitative approach with data sources originating from primary data using the observation method and secondary data using the interview method. Observation data was obtained from Instagram insight data @tukangbangunandimedan starting from November 1, 2024 to April 30, 2025, while interview data was obtained from Randy Prandana S.Kom., M.Kom as the owner of PT. Satu Shaff Bersama and founder of the @tukangbangunandimedan account. With the analysis conducted by the researcher, Instagram is a very suitable marketing channel to use. By using Instagram, PT. Satu Shaff Bersama can reach productive age consumers who have a high interest in using construction services to renovate or build new homes. Through Instagram, this company can also reduce high advertising costs and increase the company's turnover.